Incidence and clinical outcomes of bacterial superinfections in critically ill patients with COVID-19 - Yoon, Si Mong; Lee, Jinwoo; Lee, Sang-Min; Lee, Hong Yeul (Frontiers in Medicine, 2023)
Background Bacterial superinfection is not uncommon in critically ill patients with coronavirus disease (COVID-19) pneumonia requiring intensive care unit (ICU) treatment. However, there is still a lack of evidence related to bacterial superinfection and their clinical significance in critically ill patients with COVID-19. Therefore, we assessed the incidence of bacterial superinfections and their effects on clinical outcomes in critically ill patients with COVID-19. Materials and methods This single-center retrospective cohort study analyzed critically ill patients with COVID-19 admitted to the ICU at a tertiary academic hospital between February 2020 and December 2021. We reviewed data including patient demographics, clinical and microbiological characteristics, and outcomes. Results During the study period, 106 patients (median [IQR] age, 67 [58–75] years) were included, of which 32 (30%) were diagnosed with bacterial superinfections. Of these, 12 cases (38%) were associated with multidrug-resistant pathogens. Klebsiella aerogenes (6 cases [19%]) and Klebsiella pneumoniae (6 cases [19%]) were the most common pathogens associated with superinfections. The median time to bacterial superinfection was 13 (IQR, 9–20) days after ICU admission. Patients with bacterial superinfections had significantly fewer ventilator-free days on day 28 (0 [IQR, 0–0] days) than those without bacterial superinfections (19 [IQR, 0–22] days) (p < 0.001). Patients with bacterial superinfections had a longer ICU length of stay (32 [IQR, 9–53] days) than those without bacterial superinfections (11 [IQR, 7–18] days) (p < 0.001). Additionally, they had a longer hospital length of stay after ICU admission (39 [IQR, 18–62] days) than those without bacterial superinfections (18 [IQR, 12–37] days) (p = 0.001). There were no differences in ICU mortality or in-hospital mortality between the two groups. In the multivariable analysis, higher SAPS II score (OR, 2.697; 95% CI, 1.086–6.695) and thrombocytopenia (OR, 3.318; 95% CI, 1.355–8.123) were identified as risk factors for development of bacterial superinfection. Conclusion In critically ill patients with COVID-19, bacterial superinfections were common, and more than one-third of the bacterial superinfection cases were caused by multidrug-resistant pathogens. As patients with bacterial superinfections had worse clinical outcomes, the development of bacterial superinfections should be actively monitored.